Endogenous FDI Spillovers from Japan to Russia and China with Spillover-Prevention Costs - Kiyoshi Matsubara (European Regional Science Association (ERSA), 2014)
This paper explores the role of FDI-spillover prevention costs in the strategic choice for a MNE of a developed country such as Japan about whether it perform FDI to an emerging economy such as Russia and China and about a degree of FDI spillovers that it allows. After discussing the exogenous spillover case in a duopoly model, this paper shows that with a quadratic prevention cost function, the MNE may choose a positive level of spillovers lower than the benchmark exogenous level, and also shows how endogenizing spillovers affect the home firmfs decision on plant location. In the m-FDI-host-country firm case, the effects of the number of FDI-host country firms on the level of spillovers and the cutoff value of trade cost are not always monotonic.
Keywords: F12; F23; O33; 330; FDI; Endogenous Spillovers; Spillover-prevention Costs